Peningkatan Motivasi Hasil Belajar Ekonomi Melalui Model Pembelajaran Student Centered Learning - Mastufah, Mastufah (CV. Creative Tugu Pena, 2019)
In the process of learning Economics (Accounting) required a certain strategy and strong motivation. Teachers play a very important role, especially in terms of designing learning scenarios. Teachers should be able to choose a learning model that can increase the motivation of learners, in accordance with the characteristics of subjects, and characteristics of learners so that learning can take place optimally. The aim of this classroom action research is to improve the learning of learners using the student centered learning model. This research was conducted in class XI IPS1, MAN 1 Cilegon semester 1, material Posting from Juku Kebuku Besar Journals, post to a subsidiary